One‐Pot Synthesis of Propyl‐Sulfonic Phosphotungstic Dual‐Acid Functionalized Mesoporous Silica in Non‐Hydrochloric Acid Solution: Reusable Catalyst for Efficient Biodiesel Production. Issue 46 (10th December 2020) - Yu, Zhengfei; Zhang, Yibo; Duan, Jinchen; Chen, Xifeng; Piao, Mingjun; Hu, Jianglei; Shi, Fengwei
Abstract: Ordered mesoporous silica molecular sieve (HPW/OMS‐SO3 H), functionalized by phosphotungstic acid (HPW) and propyl sulfonic acid, was successfully synthesized using the green and efficient one‐pot co‐condensation method in a non‐hydrochloric acid solution. The materials, making HPW and propyl sulfonic acid successfully immobilized on the OMS supports, have ordered 2D hexagonal mesoporous structure. The catalyst showed excellent catalytic activity in the esterification of oleic acid with methanol due to the synergistic effect between the HPW and propyl sulfonic acid group. The catalytic performance not reduced significantly after five recycling reflected that the catalyst has excellent stability. The activation energy of esterification was calculated by detailed kinetic studies. Abstract : The propyl‐sulfonic‐phosphotungstic dual‐acid‐functionalized ordered mesoporous silica catalyst was synthesized in a non‐hydrochloric acid solution. This catalyst showed excellent activity and stability in esterification reaction of oleic acid with methanol.